KEPARAHAN AKNE VULGARIS DENGAN PENGGUNAAN PROBIOTIK ORAL - Elvantie; Arini Astasari Widodo; Budiman Hartono (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Background. Oral probiotics are microorganisms that have various benefits based on theoretical evidence of the skin, brain, and gut. Oral probiotics are an effective choice in the management of acne vulgaris, which has been proven by studies that state that oral probiotics can reduce the degree of acne, inflammatory lesions, non-inflammatory lesions and reduce excess sebum production. Method. The research articles reviewed are in the form of analytical reviews through the PubMed and Google Scholar databases. Results. A total of 6 research articles were selected according to the purpose of writing this literature review. Conclusion. The use of oral probiotics can reduce inflammatory lesions, the degree of severity of acne vulgaris, total inflammatory lesions, and reduce excessive sebum production. Oral probiotics, in some cases, can cause side effects such as gastrointestinal disturbances in the form of bloated. Probiotics are measured in colony-forming units (CFU) which indicate the number of viable cells. The dosage concentration of each probiotic varies, but oral probiotics still provide an effective effect on the treatment of acne vulgaris.